2017
DOI: 10.1002/jbm.a.36194
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis for postoperative temporal bone defects using human ear adipose‐derived stromal cells and tissue engineering: An animal model study

Abstract: Mastoidectomy, the removal of infected mastoid bones, is a common surgical procedure for the treatment of chronic otitis media. Persistent and recurrent otorrhea and accumulation of keratin debris following open cavity mastoidectomy are still bothersome issues for both patients and otologists. In this study, we used human ear adipose-derived stromal cells (hEASCs) in combination with polycaprolactone (PCL) scaffolds and osteogenic differentiation medium (ODM) to regenerate temporal bone defects. The hEASCs sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%
“…All efforts were made to minimize the number of animals used and their suffering. The animal models for mastoidectomy followed our previous study [ 34 ]. Briefly, SD rats were anesthetized with an intraperitoneal injection of Zoletil 50 (0.1 cc/100 g; Virvac Laboratories, Carros, France) and 2% Rompun (0.2 cc/100 g; Bayer Korea, Ansan, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that the osteogenic differentiation of hASCs can be guided by nanoparticles with a specific diameter of 200 nm [ 309 ]. It was also shown that the combination of hASCs with polycaprolactone (PCL) scaffolds allowed the anatomical and functional reconstruction of post-operative temporal bone defects after mastoidectomy (removal of infected mastoid bones) [ 256 ]. Interestingly, advances have recently been made in work on the shape-memory of polymers (polymeric intelligent materials that have the ability to return from a deformed state to their original shape due to the induction of an external stimulus).…”
Section: Adipose Stem Cells and Regenerative Medicinementioning
confidence: 99%